Effect of Combined Exercise Training and Curcumin Supplementation on Metabolic Indices and Serum Levels of Sirtuin 1 in Men with Metabolic Syndrome - Saeid Shamlou Kazemi; Ali Heidarianpour; Hanieh Naddaf; Fereshteh Mehri; Homa Naderifar (پزشکی بالینی ابن سینا, 2023)
Background and Objective: Sirtuin1 is one of the important indicators involved in metabolic control, obesity prevention, and homeostasis control. This study aimed to investigate the effect of combined exercises and curcumin consumption on metabolic indices and serum levels of Sirtuin1 in men with metabolic syndrome. Materials and Methods: The present study was conducted as a clinical trial in men with metabolic syndrome in three intervention groups and one control group. The people in the intervention group underwent an exercise program for 8 weeks and three sessions a week, the supplement group took 3 capsules of 500 mg daily. Blood factors were measured before and after the last training session. Data were analyzed by paired t-test, analysis of variance and covariance. Results: A significant difference was observed in the intra-group changes of the studied variables (Sirtuin1, HDL, LDL, TG, FBS, and TC) in all three intervention groups (P≥0.05). The results of analysis of covariance test showed a significant difference between the four groups in the indices (Sirtuin1, HDL, LDL, TG, FBS, and TC) after the test (P<0.05). Conclusion: Combined exercises, curcumin consumption, and implementation of both interventions simultaneously positively affected the metabolic indices and serum levels of Sirtuin1 in people with metabolic syndrome.